2020
DOI: 10.3390/su122410608
|View full text |Cite
|
Sign up to set email alerts
|

Application of Factor Analysis for Characterizing the Relationships between Groundwater Quality and Land Use in Taiwan’s Pingtung Plain

Abstract: Although the average municipal water coverage in Taiwan is quite high, at 93.91%, only around half of the residents in the Pingtung Plain use tap water originating from the Taiwan Water Corporation to meet their needs. This means the exploitation of a substantial amount of groundwater as a source of water to meet drinking, agriculture, aquaculture, and industry requirements. Long-term groundwater quality surveys in Taiwan have revealed obvious contamination of the groundwater in several locations in the Pingtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Factor Analysis was used for data reduction to determine the dominant use or uses of water. Jia et al, (2016, Liang et al, (2020 and Ogunbode et al (2023) conjectured that factor analysis is very relevant for appraising water use efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Factor Analysis was used for data reduction to determine the dominant use or uses of water. Jia et al, (2016, Liang et al, (2020 and Ogunbode et al (2023) conjectured that factor analysis is very relevant for appraising water use efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Factor analysis was used to interpret commonly collected data on groundwater quality and to correlate these data to a specific hydrogeological process [22]. The procedure of FA has previously been presented in the works of Davis, 1973, andBrown, 1998 [23].…”
Section: Statistical Analysis Of Water Quality Datamentioning
confidence: 99%
“…In China and Taiwan, emphasis is placed on groundwater due to drinking water shortages [28]. Studies of the latter have shown the presence of components such as: arsenic both in the water itself and in fish swimming in it; nitrates, chloride, and sodium ions, as well as iron and manganese, which in excessive amounts significantly alter the taste of the water and inhibit crop growth [28]. Pollution is mainly the result of mismanagement of industrial materials and products and of progressive urbanisation.…”
Section: Literature Reviewmentioning
confidence: 99%